Chemotherapy-Induced Bone Marrow Suppression: A Bibliometrics Analysis - Yue J; Shui H; Li G; Yang B; Tang D (Journal of Multidisciplinary Healthcare)
Jing Yue,1 Huili Shui,2 Gao Li,2 Bing Yang,2 Dongxin Tang1 1The First Clinical Medical School of Guizhou University of Traditional Chinese Medicine, Guizhou University of Traditional Chinese Medicine, Guiyang, People’s Republic of China; 2Department of Oncology, First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, People’s Republic of ChinaCorrespondence: Dongxin Tang, Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou Province, People’s Republic of China, Email dongxintang0319@163.comObjective: This study seeks to investigate the key research hotspots and evolving trends in chemotherapy-induced bone marrow suppression over the past two decades by employing bibliometric visualization analysis, thereby providing a robust theoretical and empirical foundation for advancements in both scientific understanding and clinical practice.Methods: Utilizing the Web of Science Core Database, a total of 6,110 documents were retrieved and analyzed using CiteSpace and VOSviewer software. This analysis traces and evaluates the current research status, key advancements, and development trajectories of chemotherapy-induced bone marrow suppression research from 2004 to 2023.Results: The analysis included 6,110 documents, revealing a significant upward trend in research volume. The United States (1,688 papers) and China (1,528 papers) are the leading contributors, with Cancer Chemotherapy and Pharmacology being the most prolific journal. Keyword burst detection identified key research focuses, including nasopharyngeal carcinoma, immunotherapy, and agents such as nivolumab and pembrolizumab. These findings indicate promising directions for further exploration, such as immunotherapy for nasopharyngeal carcinoma and innovative strategies for managing bone marrow suppression with specific drugs.Conclusion: Future research may concentrate on immune checkpoint inhibitors and nasopharyngeal carcinoma. Additionally, new treatment such as the natural compound curcumin has demonstrated protective effects during chemotherapy, effectively alleviating side effects. Nutritional support strategies significantly enhance patients’ quality of life during treatment, while integrative approaches that combine traditional Chinese medicine with modern medical practices reveal the potential for synergistic effects. Together, these strategies could improve clinical outcomes and effectively address the challenges posed by chemotherapy-induced bone marrow suppression.Keywords: chemotherapy-induced bone marrow suppression, bibliometric analyses, visualization, citespace, VOSviewer